The incidence of congenital syphilis in the United Kingdom: February 2010 to January 2015. (2nd March 2016) - Simms, I; Tookey, PA; Goh, BT; Lyall, H; Evans, B; Townsend, CL; Fifer, H; Ison, C
Abstract : Objective: To estimate the incidence of congenital syphilis in the UK. Design: Prospective study. Setting and population: United Kingdom. Methods: Children born between February 2010 and January 2015 with a suspected diagnosis of congenital syphilis were reported through an active surveillance system. Main outcome measures: Number of congenital syphilis cases and incidence. Results: For all years, reported incidence was below the WHO threshold for elimination (<0.5/1000 live births). Seventeen cases (12 male, five female) were identified. About 50% of infants (8/17) were born preterm (<37 weeks' gestation): median birthweight 2000 g (865–3170 g). Clinical presentation varied from asymptomatic to acute disease, including severe anaemia, hepatosplenomegaly, rhinitis, thrombocytopaenia, skeletal damage, and neurosyphilis. One infant was deaf and blind. Median maternal age was 20 years (17–31) at delivery. Where maternal stage of infection was recorded, 6/10 had primary, 3/10 secondary and 1/10 early latent syphilis. Most mothers were white (13/16). Country of birth was recorded for 12 mothers: UK ( n = 6), Eastern Europe ( n = 3), Middle East ( n = 1), and South East Asia ( n = 2). The social circumstances of mothers varied and included drug use and sex work. Some experienced difficulty accessing health care. Conclusion: The incidence of congenital syphilis is controlled and monitored by healthcare services and related surveillance systems, and is now below the WHO elimination threshold. However, reducing the public health impact of this preventable disease in the UK is highly dependent on the successful implementation of WHO elimination standards across Europe. Tweetable abstract: Congenital syphilis incidence in the UK is at a very low level and well below the WHO elimination threshold. Tweetable abstract: Congenital syphilis incidence in the UK is at a very low level and well below the WHO elimination threshold.